Biosintesis Nanopartikel ZnO Menggunakan Ekstrak Daun Tanaman Jagung (Zea Mays L.) - Adeningrum, Della Arista; Rosa, Aulia; Wahyusi, Kindriari Nurma; Yogaswara, Rachmad Ramadhan (Jurnal Fisika Unand, 2025)
ZnO nanoparticles can be synthesized using the biosynthesis method using corn plant leaf extract (Zea Mays L.) as a bioreductant. The aim of this research is to examine the effect of variations in Zinc Nitrate Hexahydrate precursor concentration and calcination temperature on the yield, as well as the characterization of ZnO nanoparticles. Corn plant leaves are extracted to obtain flavonoid compounds. The resulting extract is mixed with the precursor solution then calcined to obtain ZnO nanoparticles.  The highest yield was produced in a sample with a precursor concentration of 0.1M with a calcination temperature of 300˚ C of 22.6082%. SEM-EDX results on samples with a precursor concentration of 0.3 M and a calcination temperature of 700˚C show various particle morphologies and sizes of ZnO nanoparticles, namely 91 nm; 97 nm; 109 nm; 435nm; and 973 nm, and the composition of ZnO nanoparticles consists of 76.43% Zn atomic weight and 23.57% O ​​atomic weight. at a calcination temperature of 700˚ C shows a pure ZnO sample with an element composition of 80.3% Zn atomic weight and 19.7% O atomic weight. The size of the crystal diameter for XRD analysis on samples with a precursor concentration of 0.3M with calcination temperatures of 300 ˚C and 700˚ C were 40.8564 nm and 31.7203 nm, respectively. Both samples have the same crystal system, namely hexagonal zincite.